Kekuatan financial tehnology dalam Meningkatkan Kinerja Bisnis UMKM - Wilda Sinta Amilia; Rr. Iramani (Journal of Business & Banking, 2025)
Micro, Small and Medium Enterprises contribute greatly to driving the regional economy and providing employment opportunities for the community. Therefore, research to improve the performance of MSMEs is still very relevant to do. This study aims to examine the importance of financial technology, financial literacy, and culture in improving the business performance of MSMEs in East Java. Business performance studies that combine financial literacy, financial technology and culture with business performance, especially in the East Java region, are still very limited. Therefore, this research is important to be conducted to enrich empirical findings related to business performance. The sampling technique used was purposive sampling, by taking samples of MSMEs in the Surabaya, Mojokerto, Sidoarjo and Gresik areas. Total sample of 100 MSMEs. The data source used is primary data collected by survey using a questionnaire. Analysis was conducted with Partial Least Square. The results showed that financial technology and financial literacy as well as culture have a significant positive effect on MSME business performance. The results of this study imply that to improve the sustainability and business performance of MSMEs in East Java, MSME managers should improve their financial technoly and financial literacy capabilities and foster a culture that is the value of their business.